Electrocatalytic performance optimization of passive iron nanoparticles by Ni doping - Li, Qixiang (Nanyang Technological University, 2023)
Passive materials are typically not desirable in the field of electrocatalysis. This study presents a novel approach to enhance the oxygen evolution reaction (OER) performance of passive iron nanoparticles by doping with nickel using pulsed irradiation. The doped nanoparticles transform into spinal – type NiFe_2 O_4 nanoparticles. The Ni-doped iron nanoparticles exhibit remarkable OER activity at a low overpotential of only 1.49 V, achieving a current density of 10 mA cm^(-2) with a performance degradation of 13% after exposure to a 1M KOH solution for more than 50 hours. However, the size and uniformity of the nanoparticles are highly influenced by the heat energy dispersion of pulsed laser irradiation. Therefore, careful selection of substrate and laser parameters, and thorough consideration of the influence of the pre-deposited material layer is necessary to minimize this effect. Overall, this project offers a sustainable and efficient method to optimize passive iron nanoparticles and synthesize highly efficient OER catalysts.